Industry volatility and international trade - Adina Ardelean; Miguel A. León-Ledesma; Laura Puzzello (University of Kent, School of Economics, 2017)
We develop an empirical framework that allows us to account for producer-country, industry, and demand shocks as drivers of volatility at the industry level in open economies. Our methodology separately accounts for demand shocks originating in the home and foreign markets. Using a panel of manufacturing and trade data, our findings suggest that, independent of the level of aggregation, output volatility is driven primarily by shocks originating in the destination markets for an industry's sales (demand shocks) including home markets. Further, we show that industries more open to trade are more volatile because intra-industry imports increase the uncertainty of 1) domestic demand, and 2) production through greater exposure to foreign shocks.
Keywords: F15; F44; F61; 330; Output Volatility; Demand Shocks; Trade; Industry-level Data